Thermally responsive shape memory fiber / magnesium phosphate composite bone cement, preparation method and application thereof
Patent Information
- Application Number
- CN202311820326.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-27
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-12-27
AI Technical Summary
但是仍无法解决磷酸镁骨水泥的反应温度高的问题
[0020](1) The thermal response shape memory fiber after stretching and “programming” needs to absorb heat to return to its initial shape (shrinkage), while the hydration reaction of magnesium phosphate bone cement needs to release heat. The combination of the two can achieve temperature control when using thermal response shape memory fiber/magnesium phosphate composite bone cement.
Smart Images

Figure CN117771426B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to bone defect repair materials, and more specifically to a bone cement composite material with high strength, high porosity and low reaction temperature. Background Technology
[0002] Bone defects refer to the disruption of the integrity of bone structure caused by congenital or acquired factors. There are various causes of bone defects, including acute bone loss, debridement following bone infection, and nonunion or loss of blood supply to the bone after radiotherapy or bone tumor resection. Despite advancements in tissue engineering and other medical fields in recent years, bone defects remain a difficult condition to treat, and the amputation rate remains high.
[0003] Bone tissue engineering is a rapidly developing biotechnology in recent years, aiming to prepare biofunctional materials that can be integrated and degraded in vivo to treat diseased or damaged biological tissues. Among numerous bone repair materials, bone cement is an ideal artificial bone repair material due to its good biocompatibility and direct injection capabilities. Magnesium phosphate cement (MPC, a bone cement formed by the hydration reaction of magnesium oxide particles, phosphate powder, and water) is considered one of the most promising bone defect repair materials due to its unique advantages such as high strength, rapid degradation rate, good bone adhesion, and ability to stimulate osteoblast differentiation. However, the hydration reaction of magnesium phosphate cement is a classic acid-base reaction, which generates a large amount of heat, potentially causing secondary harm to patients. Furthermore, magnesium phosphate cement lacks a suitable porous structure for cell ingrowth and has a low porosity, affecting the repair function of bone tissue. Therefore, researchers have increased the size of magnesium oxide particles and reduced the hydration reaction rate of magnesium phosphate cement to allow for a slower release of reaction heat, thereby lowering the hydration temperature. While these methods effectively lower the hydration temperature of magnesium phosphate bone cement, they struggle to balance the cement's porosity and mechanical properties. Patent document CN103668940A, published on March 26, 2014, discloses a surface-modified fiber-reinforced composite bone cement, its preparation method, and its applications. Although the surface-modified polymer fibers significantly improve the compressive strength of the bone cement, they still cannot solve the problem of the high reaction temperature of magnesium phosphate bone cement. Therefore, to achieve control over the reaction temperature of magnesium phosphate bone cement, a different approach is necessary. Summary of the Invention
[0004] To address the aforementioned limitations of existing technologies, this invention provides a thermally responsive shape memory fiber / magnesium phosphate composite bone cement and its preparation method. This bone cement composite material comprises shape memory polymer fibers with different aspect ratios. After programming, these fibers can shrink during the bone cement curing process. By adjusting the diameter and length of the fibers in the composite material, magnesium phosphate composite bone cement with different setting temperatures, porosities, and pore structures can be obtained. Simultaneously, the magnesium phosphate composite bone cement not only possesses suitable porosity and pore structure for cell growth and a low setting temperature, but also exhibits higher mechanical properties. This achieves the goal of increasing the mechanical properties and porosity of the bone cement while simultaneously regulating its setting temperature, thus providing a novel material for bone defect repair.
[0005] To address the aforementioned technical problems, this invention proposes a thermally responsive shape memory fiber / magnesium phosphate composite bone cement. This composite bone cement comprises thermally responsive shape memory fibers, magnesium oxide, and potassium dihydrogen phosphate, with a weight ratio of (100–140):100:(5–11). The thermally responsive shape memory fibers are prepared by electrospinning of shape memory polymers, with a diameter of 500 nm–3 μm and a length of 500 μm–6 mm. The composite bone cement is prepared using a one-step method, exhibiting a compressive strength of 70–120 MPa, a porosity of 15–40%, and a setting temperature of 40–55 °C.
[0006] Furthermore, in the composite bone cement of the present invention, wherein:
[0007] The weight percentage of the thermally responsive shape memory fiber is preferably 3.3% to 3.8%.
[0008] The diameter of the thermally responsive shape memory fiber is preferably 500 nm, and the length is preferably 3 mm.
[0009] The shape memory polymer is any one of polycaprolactone, polylactic acid-glycolic acid copolymer, polyurethane, and poly(p-dioxanone). Polycaprolactone is preferred.
[0010] Furthermore, this invention also proposes a method for preparing the aforementioned thermally responsive shape memory fiber / magnesium phosphate composite bone cement, comprising the following steps:
[0011] 1) Preparation of electrospun membranes with an average fiber diameter of 500 nm to 3 μm: After mixing shape memory polymer and crosslinking agent, the mixture is dissolved in solvent at a weight-volume ratio of 10 to 20 g / 100 mL and stirred until completely dissolved to obtain a homogeneous polymer solution; electrospinning technology is used to obtain electrospun membranes with an average fiber diameter of 500 nm to 3 μm, and stored at -80 °C in the dark;
[0012] 2) Preparation of thermally responsive shape memory fibers with a length of 500μm to 6mm: The electrospun membrane obtained in step 2) is mixed with water, and the fibers with a length of 500μm to 6mm are obtained by freeze-pulverization, which are thermally responsive shape memory fibers.
[0013] 3) Preparation of bone cement slurry: The bone cement slurry comprises a solid mixture and a liquid phase with a weight-to-volume ratio of 3 g / ml; wherein, the solid mixture is prepared by weighing magnesium oxide, potassium dihydrogen phosphate and thermally responsive shape memory fiber in a weight ratio of (100-140):100:(5-11), mixing them evenly, and the liquid phase is deionized water.
[0014] Furthermore, in the preparation method described in this invention, step 1) specifically involves: weighing shape memory polymer, xylene ketone, and triallyl isocyanurate at a weight ratio of 50:1:1, mixing them evenly to obtain mixture A, dissolving mixture A in a solvent at a weight-to-volume ratio of 10-20 g / 100 mL, stirring for 3 hours to obtain a homogeneous polymer phase; and using electrospinning technology to obtain spun fibers with an average diameter of 500 nm to 3 μm. The electrospinning process conditions are: solution flow rate of 0.4 mL / min, spinning voltage of 10 kV, spinning distance of 15 cm, and ambient humidity of 10%.
[0015] In step 1), the solvent is composed of a mixture of dichloromethane and N,N-dimethylformamide in a volume ratio of 7:3.
[0016] In step 2), the process conditions of the freezing and pulverizing method are as follows: the electrospun film is mixed with water and frozen into ice blocks at -80°C. The ice blocks are then pulverized using a pulverizer, and the pulverization is repeated 3 to 6 times.
[0017] The composite bone cement prepared by the method described in this invention is used for bone defect repair. The application process is as follows: the solid mixture is mixed with deionized water at a weight-to-volume ratio of 3 g / ml, and stirred at 10-30°C for 40-60 seconds under ultrasonic conditions to obtain bone cement slurry. The bone cement slurry is then immediately filled into a syringe, injected into a membrane, and cured at 37°C and 90% humidity for 72 hours.
[0018] Within 30 minutes of mixing the solid mixture with deionized water, the reaction between magnesium oxide and potassium dihydrogen phosphate releases heat, while the thermally responsive shape memory fiber absorbs heat, resulting in a solidification temperature of 40–55°C. After absorbing heat, the thermally responsive shape memory fiber shrinks, forming pores inside the composite bone cement with a porosity of 15–40%.
[0019] Compared with the prior art, the beneficial effects of the present invention are:
[0020] (1) The thermal response shape memory fiber after stretching and “programming” needs to absorb heat to return to its initial shape (shrinkage), while the hydration reaction of magnesium phosphate bone cement needs to release heat. The combination of the two can achieve temperature control when using thermal response shape memory fiber / magnesium phosphate composite bone cement.
[0021] (2) Since thermally responsive shape memory fibers can shrink under thermal stimulation, they will form pores inside the thermally responsive shape memory fiber / magnesium phosphate composite bone cement, thereby increasing the porosity of the thermally responsive shape memory fiber / magnesium phosphate composite bone cement.
[0022] (3) Introducing fiber materials into the matrix can enhance the mechanical properties of the matrix. The thermally responsive shape memory fiber / magnesium phosphate composite bone cement prepared by this invention has the advantage of higher compressive strength than magnesium phosphate bone cement.
[0023] (4) The thermally responsive shape memory fiber / magnesium phosphate composite bone cement prepared by the present invention has a suitable pore structure and porosity, and has better biocompatibility compared with magnesium phosphate bone cement. Attached Figure Description
[0024] Figure 1 These are SEM images of the thermally responsive shape memory polymer fibers from Example 1;
[0025] Figure 2 This is a SEM image of the thermally responsive shape memory fiber / magnesium phosphate composite bone cement from Example 6;
[0026] Figure 3 Examples 4, 5, and 6 show the temperature-time curves of thermally responsive shape memory fiber / magnesium phosphate composite bone cement compared to conventional magnesium phosphate bone cement.
[0027] Figure 4 The porosity of thermally responsive shape memory fiber / magnesium phosphate composite bone cement in Examples 2, 3, and 4 compared to that of conventional magnesium phosphate bone cement;
[0028] Figure 5 The mechanical properties of thermally responsive shape memory fiber / magnesium phosphate composite bone cement in Examples 1, 2 and 4 compared to conventional magnesium phosphate bone cement are shown.
[0029] Figure 6 This is a fluorescence image of the in vitro cell experiment of thermally responsive shape memory fiber / magnesium phosphate composite bone cement in Example 2;
[0030] Figure 7 This is the cell proliferation status (CCK-8) of the thermally responsive shape memory fiber / magnesium phosphate composite bone cement in Example 2. Detailed Implementation
[0031] The design concept of this invention, a thermoresponsive shape memory fiber / magnesium phosphate composite bone cement, is as follows: by combining thermoresponsive shape memory biopolymers with magnesium phosphate bone cement, it is expected to significantly improve the compressive strength of the bone cement while solving the problem of high reaction temperature in magnesium phosphate bone cement. The so-called thermoresponsive shape memory biopolymer is a smart polymer material that, under set conditions, acquires a temporary shape through "programming," and then returns to its initial shape under thermal stimulation. The most significant characteristic of this material is that, after pre-programming, it can absorb heat and recover its shape according to a designed path. Therefore, if shape memory fibers are introduced into magnesium phosphate bone cement, the heat of hydration of magnesium phosphate bone cement can drive the pre-set thermoresponsive shape memory recovery (shrinkage) of the fibers, thereby controlling the reaction temperature of magnesium phosphate bone cement; secondly, the pre-set thermoresponsive shape memory recovery (shrinkage) of the fibers themselves can enable the composite bone cement to obtain a pre-set pore structure; finally, introducing fiber materials into the matrix is itself a common and effective way to enhance the mechanical properties of the matrix. Therefore, it can be seen that by combining magnesium phosphate bone cement with thermally responsive shape memory fibers, the high reaction temperature of MPC and the heat absorption required during the shape recovery process of thermally responsive shape memory polymer microfibers can be utilized to drive the fibers to undergo thermally responsive shape memory recovery (shrinkage). This not only allows for precise control of the hydration temperature of magnesium phosphate bone cement by regulating its reaction temperature, but also creates the necessary porous structure for bone repair due to fiber shrinkage. Furthermore, the fiber reinforcement enhances the mechanical properties of MPC, promoting bone tissue repair.
[0032] This invention proposes a thermoresponsive shape memory fiber / magnesium phosphate composite bone cement that achieves high mechanical properties while maintaining suitable porosity, thereby promoting osteoblast proliferation and accelerating bone tissue healing. The composite bone cement comprises thermoresponsive shape memory fibers, magnesium oxide, and potassium dihydrogen phosphate in a weight ratio of (100–140):100:(5–11). The thermoresponsive shape memory fibers are prepared by electrospinning of shape memory polymers, with a diameter of 500 nm–3 μm and a length of 500 μm–6 mm. The composite bone cement is prepared using a one-step method, exhibiting a compressive strength of 70–120 MPa, a porosity of 15–40%, and a setting temperature of 40–55 °C. The preparation method mainly includes: First, using shape memory polymers, an electrospun membrane with an average fiber diameter of 500 nm to 3 μm is obtained using electrospinning technology. Then, shape memory fibers with a length of 500 μm to 6 mm are obtained using a freeze-thaw method. Next, a solid mixture is obtained according to the weight ratio of shape memory fibers, magnesium oxide, and potassium dihydrogen phosphate of (100–140):100:(5–11). The solid mixture is dissolved in deionized water at a mass-to-volume ratio of 3 g / mL, and after ultrasonic stirring, bone cement slurry is obtained. In the above preparation process, by controlling the uniform composite of different amounts of shape memory fibers in magnesium phosphate bone cement, composite bone cement containing different shape memory fibers can be obtained.
[0033] The composite bone cement prepared by the method of the present invention can achieve high mechanical properties while obtaining a suitable porosity, thereby promoting osteoblast proliferation and accelerating bone tissue healing.
[0034] In this invention, the setting temperature, mechanical properties, and porosity of magnesium phosphate composite bone cement are adjusted by regulating the fiber content. Furthermore, the setting temperature of the composite bone cement decreases as the fiber diameter increases. The higher the fiber content and the longer the fiber length, the higher the porosity and mechanical properties of the composite bone cement.
[0035] In this invention, the shape memory fiber is prepared from any one of the following polymers: polycaprolactone, polylactic acid-hydroxyacetic acid copolymer, polyurethane, and poly(p-dioxanone).
[0036] The thermally responsive shape memory fiber-magnesium phosphate composite bone cement prepared by this invention possesses high mechanical properties, providing postoperative mechanical support to patients. Secondly, the setting temperature can stimulate the shape memory fibers to recover their shape, creating a suitable porosity and pore structure for cell growth within the magnesium phosphate bone cement. Finally, adjusting the setting temperature during the bone cement's solidification process can be used as a thermotherapy to kill residual bone tumor cells after surgery. The composite bone cement prepared by this invention shows great promise for use in bone defect repair.
[0037] The present invention will be specifically described below through embodiments. It should be noted that these embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments based on the above content of the present invention.
[0038] Example 1:
[0039] The steps for preparing thermally responsive shape memory fiber-magnesium phosphate composite bone cement are as follows:
[0040] 1) Preparation of shape memory fibers with a diameter of 500 nm: Weigh 10 g of polycaprolactone, 0.2 g of xylene ketone, and 0.2 g of triallyl isocyanurate, and dissolve them in 100 mL of solvent. The solvent is a mixed solvent of dichloromethane and N,N-dimethylformamide (DCM:DMF = 7:3). Stir for 3 h to obtain a homogeneous polymer phase; use electrospinning technology to obtain spun fibers with an average diameter of 500 nm, wherein the solution flow rate is 0.4 mL / min, the spinning voltage is 10 kV, the spinning distance is 15 cm, and the ambient humidity is 10%.
[0041] 2) Preparation of shape memory fibers with a length of 6 mm: The pretreated electrospun membrane was mixed with water and frozen into ice at -80℃. The ice was then crushed using a pulverizer. This process was repeated three times to obtain shape memory fibers with an average diameter of 500 nm and a length of 6 mm. The SEM image is shown below. Figure 1 As shown.
[0042] 3) Preparation of thermally responsive shape memory fiber / magnesium phosphate composite bone cement: Weigh 10g of magnesium oxide, 10g of potassium dihydrogen phosphate, and 0.5g of polycaprolactone fiber, and mix the solid phases thoroughly. Then, measure 6.8mL of deionized water and mix it with the solid phase. Immediately, stir the mixture while sonicating at 20℃ for 1min to obtain the bone cement slurry. Inject the slurry into a mold using a syringe and cure it in a constant temperature and humidity chamber at 37℃ and 90% humidity for 72h. After drying, the obtained composite bone cement is sealed and stored.
[0043] After testing with a universal testing machine, the thermal response shape memory fiber / magnesium phosphate composite bone cement obtained in Example 1, as shown in the following tests... Figure 5 As shown, its compressive strength is 116 MPa; using Archimedes' displacement method, the porosity of the thermally responsive shape memory fiber / magnesium phosphate composite bone cement obtained in Example 1 is 15.5%; and the setting temperature is 53°C as measured by a microprobe thermometer.
[0044] Example 2:
[0045] The thermally responsive shape memory fiber-magnesium phosphate composite bone cement was prepared using a process essentially the same as in Example 1, with the only difference being:
[0046] In step 2), the number of times the ice cube is crushed is increased from 3 times to 4 times to obtain shape memory fibers with an average diameter of 500nm and a length of 3mm.
[0047] In step 3), the materials used to form the solid mixture are changed from 10g of magnesium oxide, 10g of potassium dihydrogen phosphate and 0.5g of polycaprolactone fiber to 11g of magnesium oxide, 10g of potassium dihydrogen phosphate and 0.8g of polycaprolactone fiber, and the amount of deionized water is changed from 6.8mL to 7.3mL.
[0048] After testing with a universal testing machine, the thermally responsive shape memory fiber / magnesium phosphate composite bone cement obtained in Example 2, as shown in the following tests... Figure 5 As shown, its compressive strength is 91.2 MPa; using Archimedes' displacement method, the thermal response shape memory fiber / magnesium phosphate composite bone cement obtained in Example 2, as shown... Figure 4 As shown, the porosity is 39.7%; the solidification temperature is 50℃, as determined by a microprobe thermometer.
[0049] Example 3:
[0050] The thermally responsive shape memory fiber-magnesium phosphate composite bone cement was prepared using a process essentially the same as in Example 1, with the only difference being:
[0051] In step 1), the amounts of shape memory polymer and crosslinking agent were changed from 10g of polycaprolactone, 0.2g of xylene ketone, and 0.2g of triallyl isocyanurate to 20g of polycaprolactone, 0.4g of xylene ketone, and 0.4g of triallyl isocyanurate. The electrospinning process conditions were changed from a solution flow rate of 0.4mL / min, a spinning voltage of 10kV, a spinning distance of 15cm, and an ambient humidity of 10% to a solution flow rate of 0.6mL / min, a spinning voltage of 17kV, a spinning distance of 20cm, and an ambient humidity of 10%, thereby obtaining shape memory fibers with a diameter of 3μm.
[0052] In step 2), the number of times the ice cube is crushed is increased from 3 times to 5 times to obtain shape memory fibers with an average diameter of 3μm and a length of 1mm.
[0053] In step 3), the ingredients for forming the solid mixture are changed from 10g of magnesium oxide, 10g of potassium dihydrogen phosphate and 0.5g of polycaprolactone fiber to 14g of magnesium oxide, 10g of potassium dihydrogen phosphate and 1g of polycaprolactone fiber, and the amount of deionized water is changed from 6.8mL to 8.3mL.
[0054] After testing with a universal testing machine, the compressive strength of the thermally responsive shape memory fiber / magnesium phosphate composite bone cement obtained in Example 3 was 80.4 MPa; using Archimedes' displacement method, the thermally responsive shape memory fiber / magnesium phosphate composite bone cement obtained in Example 3, as shown... Figure 4 As shown, the porosity is 15%; the solidification temperature, as measured by a microprobe thermometer, is 45℃.
[0055] Example 4:
[0056] The thermally responsive shape memory fiber-magnesium phosphate composite bone cement was prepared using a process essentially the same as in Example 1, with the only difference being:
[0057] In step 2), the number of times the ice cube is crushed is increased from 3 times to 6 times to obtain shape memory fibers with an average diameter of 500 nm and a length of 500 μm.
[0058] In step 3), the materials used to form the solid mixture are changed from 10g of magnesium oxide, 10g of potassium dihydrogen phosphate and 0.5g of polycaprolactone fiber to 11g of magnesium oxide, 10g of potassium dihydrogen phosphate and 0.8g of polycaprolactone fiber, and the amount of deionized water is changed from 6.8mL to 7.3mL.
[0059] After testing with a universal testing machine, the thermally responsive shape memory fiber / magnesium phosphate composite bone cement obtained in Example 4, as shown in the following tests... Figure 5 As shown, its compressive strength is 74.4 MPa; using Archimedes' displacement method, the thermal response shape memory fiber / magnesium phosphate composite bone cement obtained in Example 4, as shown... Figure 4 As shown, the porosity is 26.1%; the solidification temperature, as measured by a microprobe thermometer, is 51℃.
[0060] Example 5:
[0061] The thermally responsive shape memory fiber-magnesium phosphate composite bone cement was prepared using a process essentially the same as in Example 1, with the only difference being:
[0062] In step 1), the amounts of shape memory polymer and crosslinking agent were changed from 10g of polycaprolactone, 0.2g of xylene ketone, and 0.2g of triallyl isocyanurate to 20g of polycaprolactone, 0.4g of xylene ketone, and 0.4g of triallyl isocyanurate. The electrospinning process conditions were changed from a solution flow rate of 0.4mL / min, a spinning voltage of 10kV, a spinning distance of 15cm, and an ambient humidity of 10% to a solution flow rate of 0.6mL / min, a spinning voltage of 17kV, a spinning distance of 20cm, and an ambient humidity of 10%.
[0063] After freeze-pulverization, shape memory fibers with an average diameter of 3μm and a length of 6mm were obtained.
[0064] In step 3), the ingredients for forming the solid mixture are changed from 10g of magnesium oxide, 10g of potassium dihydrogen phosphate and 0.5g of polycaprolactone fiber to 11g of magnesium oxide, 10g of potassium dihydrogen phosphate and 0.8g of polycaprolactone fiber, and the amount of deionized water is changed from 6.8mL to 7.3mL.
[0065] The compressive strength of the thermally responsive shape memory fiber / magnesium phosphate composite bone cement obtained in Example 5 was 115.6 MPa, as tested by a universal testing machine. The porosity of the thermally responsive shape memory fiber / magnesium phosphate composite bone cement obtained in Example 5 was 28.7%, as tested by an Archimedes drainage method. The setting temperature was 40°C, as tested by a microprobe thermometer.
[0066] Example 6:
[0067] The preparation process of the thermally responsive shape memory fiber-magnesium phosphate composite bone cement is basically the same as that in Example 1, except that in step 1), the amount of shape memory polymer and crosslinking agent is changed from 10g of polycaprolactone, 0.2g of xylene ketone, and 0.2g of triallyl isocyanurate to 30g of polycaprolactone, 0.3g of xylene ketone, and 0.3g of triallyl isocyanurate; and the electrospinning process conditions are changed from a solution flow rate of 0.4mL / min, a spinning voltage of 10kV, a spinning distance of 15cm, and an ambient humidity of 10% to a solution flow rate of 0.6mL / min, a spinning voltage of 15kV, a spinning distance of 15cm, and an ambient humidity of 10%.
[0068] After freeze-pulverization, shape memory fibers with an average diameter of 3μm and a length of 6mm were obtained.
[0069] Figure 2 SEM images of the thermally responsive shape memory fiber / magnesium phosphate composite bone cement finally prepared in Example 6 are shown.
[0070] The compressive strength of the thermally responsive shape memory fiber / magnesium phosphate composite bone cement obtained in Example 6 was 117.8 MPa, as tested by a universal testing machine. The porosity of the thermally responsive shape memory fiber / magnesium phosphate composite bone cement obtained in Example 6 was 17.5%, as tested by an Archimedes drainage method. The setting temperature was 47°C, as tested by a microprobe thermometer.
[0071] Research Materials
[0072] The thermally responsive shape memory fiber / magnesium phosphate composite bone cement described above, such as Figure 1As shown, the microstructure of the thermally responsive shape memory fibers in Example 2 is illustrated. Subsequently, to demonstrate that the addition of shape memory fibers can achieve pore size, the cross-section of the thermally responsive shape memory fiber / magnesium phosphate composite bone cement was observed using field emission scanning electron microscopy (SEM). Figure 2 As shown, in Example 6, pores of varying sizes appear on the surface of the material, and a through-pore structure is generated due to the shape recovery of the shape memory polymer. Figure 3 The temperature changes between thermally responsive shape memory fiber / magnesium phosphate composite bone cement and magnesium phosphate bone cement in Examples 4, 5, and 6 are shown. It can be seen that before the thermally responsive shape memory fiber is mixed, the hydration temperature of magnesium phosphate bone cement reaches a maximum of 63°C, while the hydration reaction temperature of thermally responsive shape memory fiber / magnesium phosphate composite bone cement is a maximum of 48°C, and it is maintained at 40-43°C for more than 10 minutes. This is because potassium dihydrogen phosphate and magnesium oxide have a typical acid-base reaction, which releases a large amount of heat. The pre-programmed thermally responsive shape memory fiber needs to absorb heat when returning to the initial temperature. Therefore, the setting temperature of thermally responsive shape memory fiber / magnesium phosphate composite bone cement is lower than that of magnesium phosphate bone cement. Figure 4 The porosity of thermally responsive shape memory fiber / magnesium phosphate composite bone cement and magnesium phosphate bone cement in Examples 2, 3, and 4 are shown.
[0073] Figure 5 Examples 1, 2, and 4 compare the mechanical properties of thermally responsive shape memory fiber / magnesium phosphate composite bone cement and magnesium phosphate bone cement. It can be observed that the thermally responsive shape memory fiber / magnesium phosphate composite bone cement exhibits increased porosity and mechanical properties compared to magnesium phosphate bone cement. This is likely because the pores created by the thermally responsive shape memory fibers after recovery act as reinforcement under load (an industry consensus). Therefore, the thermally responsive shape memory fiber / magnesium phosphate composite bone cement has higher and stronger porosity and mechanical properties than magnesium phosphate bone cement. To investigate osteoblast proliferation on the material surface, such as... Figure 6 As shown in the fluorescence staining images of the material described in Example 2 at days 1, 3, and 5, it can be seen that on day 1, the cells are spindle-shaped on the material surface, indicating that the cells can adhere to the material. On days 3 and 5, the composite material described in Example 2 showed better cell compatibility than magnesium phosphate bone cement. To further corroborate this... Figure 6 The fluorescence results shown are as follows: Figure 7 The CCK-8 results shown indicate that the composite material described in Example 2 exhibited better biocompatibility on days 3 and 5. In summary, this demonstrates that the shape memory fiber / magnesium phosphate composite bone cement of this invention not only regulates the hydration reaction temperature but also possesses excellent mechanical properties and a porous structure suitable for cell adhesion and proliferation, thus promoting bone repair.
[0074] Although the present invention has been described above in conjunction with the accompanying drawings, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many changes under the guidance of the present invention without departing from the spirit of the present invention, and these changes are all within the protection scope of the present invention.
Claims
1. A method for preparing a thermally responsive shape memory fiber / magnesium phosphate composite bone cement, characterized in that, Includes the following steps: S1) Preparation of electrospun membranes with an average fiber diameter of 500 nm to 3 μm: A shape memory polymer and a crosslinking agent were mixed and dissolved in a solvent at a weight-to-volume ratio of 10–20 g / 100 mL. The mixture was stirred until completely dissolved to obtain a homogeneous polymer solution. Electrospun membranes with an average fiber diameter of 500 nm to 3 μm were obtained and stored at -80°C in the dark. Specific details are as follows: Shape memory polymer, xylene ketone and triallyl isocyanurate were weighed in a weight ratio of 50:1:1 and mixed evenly to obtain mixture A. Mixture A was dissolved in a solvent in a weight-volume ratio of 10~20 g / 100 mL and stirred for 3 h to obtain a homogeneous polymer phase. The solvent was composed of a mixture of dichloromethane and N,N-dimethylformamide in a volume ratio of 7:
3. Electrospinning technology was used to obtain spun fibers with an average diameter of 500 nm to 3 μm. The electrospinning process conditions were: solution flow rate of 0.4 mL / min, spinning voltage of 10 kV, spinning distance of 15 cm, and ambient humidity of 10%. S2) Preparation of thermally responsive shape memory fibers with a length of 500 μm to 6 mm: The electrospun membrane obtained in step 1) is mixed with water, and the fibers with a length of 500 μm to 6 mm are obtained by freeze-pulverization method, which are thermally responsive shape memory fibers. S3) Preparation of bone cement slurry: The bone cement slurry comprises a solid mixture and a liquid phase with a weight-to-volume ratio of 3 g / ml; wherein, the solid mixture is prepared by weighing magnesium oxide, potassium dihydrogen phosphate and thermally responsive shape memory fiber in a weight ratio of (100-140):100:(5-11), mixing them evenly, and the liquid phase is deionized water.
2. A thermally responsive shape memory fiber / magnesium phosphate composite bone cement, characterized in that, The composite bone cement is prepared according to the preparation method described in claim 1, comprising thermally responsive shape memory fibers, magnesium oxide, and potassium dihydrogen phosphate, in a weight ratio of (100-140):100:(5-11); the thermally responsive shape memory fibers are prepared by electrospinning of shape memory polymers, and the diameter of the thermally responsive shape memory fibers is 500 nm to 3 μm, and the length is 500 μm to 6 mm; the composite bone cement is prepared by a one-step method, and the compressive strength of the composite bone cement is 70-120 MPa, the porosity is 15-40%, and the setting temperature is 40-55℃.
3. The composite bone cement according to claim 2, characterized in that, The weight percentage of the thermally responsive shape memory fiber is 3.3% to 3.8%.
4. The composite bone cement according to claim 2, characterized in that, The thermally responsive shape memory fiber has a diameter of 500 nm and a length of 3 mm.
5. The composite bone cement according to claim 2, characterized in that, The shape memory polymer is any one of polycaprolactone, polylactic acid-glycolic acid copolymer, polyurethane, and polydioxanone.
6. The composite bone cement according to claim 2, characterized in that, The shape memory polymer is polycaprolactone.
7. An application of a thermally responsive shape memory fiber / magnesium phosphate composite bone cement, characterized in that, The composite bone cement prepared according to any one of claims 2 to 6 by the preparation method according to claim 1 is used for bone defect repair. The application process is as follows: the solid mixture is mixed with deionized water at a weight-to-volume ratio of 3 g / ml, and stirred at 10-30℃ for 40-60 s under ultrasonic conditions to obtain bone cement slurry. The bone cement slurry is then immediately filled into a syringe, injected into a membrane, and cured at 37℃ and 90% humidity for 72 h.
8. The application of the thermally responsive shape memory fiber / magnesium phosphate composite bone cement according to claim 7, characterized in that, When the solid mixture is mixed with deionized water, the reaction between the magnesium oxide and potassium dihydrogen phosphate releases heat. At the same time, the thermally responsive shape memory fiber absorbs heat, resulting in a solidification temperature of 40-55°C. After absorbing heat, the thermally responsive shape memory fiber shrinks, forming pores inside the composite bone cement with a porosity of 15-40%.
Citation Information
Patent Citations
Surface modification fiber-reinforced composite bone cement as well as preparation method and application thereof
CN103668940A
Preparation method of three-layer lead tissue regenerating velum with gradient
CN101584885A
Chemically induced pluripotent stem cells for safe therapeutic applications
US20150297638A1